Crossing Broadcasters: The Transatlantic Exchange Between Sylvester 'Pat' Weaver and Sir Ian Jacob, 1955–1956. Issue 4 (2nd October 2018) - Knox, Simone
Abstract : This article is interested in the long-standing exchange visits by broadcasters across the Atlantic, as these give insight into the developing relationships between British and US broadcasting. Informed by original archive research at the Library of Congress, Washington DC and the BBC Written Archives' Centre, Caversham, the article focuses on the charged rhetorical exchange of then-President of NBC Television, Sylvester 'Pat' Weaver (1908–2002) and then-Director General of the BBC, Sir Ian Jacob (1899–1993), in London and New York in 1955–1956. The article identifies this altercation as a foundational moment when the identities of British and US broadcasting became highlighted, performed and negotiated. Jacob and Weaver's transatlantic exchange illuminates the move from wartime cooperation to post-war global competition between the two broadcasting systems and helps to uncover the thus far marginalised history of the US pressure and influence on the arrival of commercial broadcasting in Britain. The historiographical analysis further demonstrates that Ian Jacob deserves more scholarly attention and recognition than he has received so far.